The Role of Leadership Style in Asset Misappropriation: An Ethnography Study - Adji, Azizah Fattih Rezqiyah; Chariri, Anis (Теорія та практика судової експертизи і криміналістики, 2022)
This study is an ethnography study conducted in a private con-struction company in the oil and gas sector. The study aims to uncover the socio-cultural reasons behind employee asset misappropriation in an organization. Asset misappropriation is a scheme of occupation-al fraud that often occurs repeatedly. ACFE in 2022 stated that this scheme consistently ranks first, with the number of cases up to 86 %. The main question of this research is how leadership style can shape or-ganizational culture and become one of the triggers for the emergence of acts of asset misappropriation in an organization. Furthermore, this study concludes that leaders can shape and internalize organization-al culture, and fraud as a social reality can be triggered by leadership styles. Aspects of the multi-paradigm that exist in accounting arise be-cause accounting can be combined with other sciences, one of which is forensics. Forensics is a field of science designed to aid in the process of upholding justice through the process of applying science or science. What is learned from forensic accounting not only concerns how an organization becomes a victim of fraud or how the flow of company funds can be manipulated in this way, but forensic accounting also examines the behavior of fraudsters. The purpose is that in the future, organizations can find the right way to minimize the occurrence of fraud in their environment. From this, forensic accounting has become a collection of different disciplines, such as accounting, sociology, law, culture, criminology, computer science, and psychology.